Multilocation Evaluation of Alternative Forage Crops Grown Under Salinity Conditions in the South of Morocco - El Mouttaqi, Ayoub; Mnaouer, Ihssane; Belcaid, Mohamed; Ibourki, Mohamed; Diatta, Lamine; Devkota, Krishna; Nilahyane, Abdelaziz; Hirich, Abdelaziz (Springer, 2024)
Salinity is a major problem affecting agricultural activity in many regions across the world. Therefore, practices such as biosaline agriculture and crop diversification by introducing alternative crops are key solutions to overcome this problem and enhance the productivity of salt-affected lands. This study aimed to evaluate the performance of several alternative forage crops, including cereals, pseudo-cereals, grasses, legumes, and fodder beet cultivated under saline conditions in five experimental sites in the south of Morocco. The obtained results indicated that not all crops performed very well on all sites. Crops with low tolerance to salinity, such as the cereals group, showed a significant reduction in dry biomass and yield due to increased salinity. In comparison, salt-tolerant crops such as blue panicum, sesbania, and fodder beet showed higher productivity under moderate and high salinity levels in comparison with low salinity. The findings of this study clearly indicated that the good adaptation and performance of most tested alternative crops under salinity conditions, especially the perennial crops such as blue panicum and sesbania are favored by farmers due to their low requirement in terms of agricultural inputs.